The Effect of Teacher Pedagogic Competence on the Implementation of HOTS-Based Reading and Writing Learning in High-Grade Elementary School Students - Suharni Sanusi; Aida Aziz; Munirah Munirah (Pedagogik Journal of Islamic Elementary School, 2023)
This study aims to see the effect of teacher pedagogical competence on the ability to apply HOTS-based reading and writing learning in the upper grades of elementary schools. This research is a quantitative research with the expose facto method. The research was conducted in cluster I, North Galesong District, Takalar Regency. The study population was upper class teachers in cluster I, North Galesong District, Takalar Regency, totaling 24 people. Through the cluster random sampling technique, the research sample was teachers at Public Elementary School No. 93 Sawakung Beba, totaling 3 people and public elementary school No. 94 Beba, totaling 3 people. Data collection techniques were carried out through questionnaires, observation, and documentation. Data analysis was carried out through quantitative descriptive analysis. The results showed that the teacher's pedagogical competence influenced the ability to apply HOTS-based reading and writing learning in the upper grades of Gugus I Elementary School, North Galesong District, Takalar Regency.